Modern advancements in minimally invasive surgical treatments for benign prostatic obstruction. (July 2021) - Pascoe, John; Fontaine, Christina; Hashim, Hashim
A wide variety of minimally invasive surgical techniques are now being offered for treating voiding lower urinary tract symptoms (LUTS) secondary to benign prostatic obstruction (BPO). These options offer an alternative to both medical therapy and traditional surgical options. Minimally invasive surgical treatments in LUTS/BPO boast both day case and local anaesthetic options, with a potentially reduced side effect profile compared to traditional surgical interventions matching the needs for a range of patients. We provide a narrative review of minimally invasive surgical treatments available for BPO in terms of the technology, efficacy, safety, institutional recommendations, cost and potential future developments.